(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Understanding the financial structure is one of the most important matters of interest to users of financial statements because it affects the financial performance of companies, due to the availability of many financing alternatives that the company wants to compose appropriately, and the company may be exposed to financial risks affecting the structure, which requires the external auditor to take action by determining the extent of its exposure to risks and evaluating the effectiveness of its strategies to manage those risks. The measurement process depends on different tools and methods that provide accurate insights into potential risks and their financial impact, in order to enhance the quality of the audit, which is measured by knowing the extent of compliance with auditing standards and performance standards in the audit process. And the extent of the auditor’s ability to diagnose errors and material violations in the financial statements. The link between more than one variable in this research is an important step as previous studies did not address it, and the research aims to identify audit procedures when analyzing the financial structure in the financial statements by studying the financial ratios with a statement of the effects of some economic variables, such as interest rates and inflation rates on the result of the analysis, while comparing the availability of audit quality indicators. The research relied on the applied aspect on analyzing the financial statements for three years for the research sample, which includes Ashur International Investment Bank and Al-Nokhba Company, calculating financial ratios, applying the proposed audit risk identification and assessment model, and measuring the quality of the audit as a result of the results of the analysis of the reality of external audit reports. The research reached many conclusions, namely the existence of interconnected relationships between the research variables that contribute to planning the audit in a way that enhances its quality on the other hand, and giving a true picture of the fairness of the financial statements that serve the users of those statements to make appropriate decisions. These conclusions are important in the banking and contracting sectors.